Fallen Astronauts : Heroes Who Died Reaching for the Moon, Revised Edition - Burgess, Colin, 1947-; Doolan, Kate, 1962- (Book collections on Project MUSE., 2016)
Stories of the eight American astronauts and eight Soviet cosmonauts who died in the race to reach the moon. --